Thermal Properties of Calcium Sulphoaluminate Cement as an Alternative to Ordinary Portland Cement - Małgorzata Gołaszewska (MDPI AG, 2021)
This paper presents the results of research into the heat of hydration and activation energy of calcium sulphoaluminate (CSA) cement in terms of the dependence on curing temperature and water/cement ratio. Cement pastes with water/cement ratios in the range of 0.3–0.6 were tested by isothermal calorimetry at 20 °C, 35 °C and 50 °C, with the evolved hydration heat and its rate monitored for 168 h from mixing water with cement. Reference pastes with ordinary Portland cement (OPC) were also tested in the same range. The apparent activation energy of CSA and OPC was determined based on the results of the measurements. CSA pastes exhibited complex thermal behaviour that differed significantly from the thermal behaviour of ordinary Portland cement. The results show that both the w/c ratio and elevated temperature have a meaningful effect on the heat emission and the hydration process of CSA cement pastes. The determined apparent activation energy of CSA revealed its substantial variability and dependence, both on the w/c ratio and the curing temperature.